2014
DOI: 10.1007/s00406-014-0523-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of anxiety disorders in German-speaking countries: current status and changes between 1994 and 2011

Abstract: Over the past years, international treatment guidelines have been established for the treatment of anxiety disorders. Nevertheless, little is known as to whether the actual inpatient treatment follows these guidelines. The main goal of this study was to answer the question whether patients with anxiety disorder are treated according to treatment guidelines. A total of 2,573 psychiatric inpatients with the diagnosis of anxiety disorder (920 men, 1,653 women) were identified on the basis of the data of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Anyhow, there still is a need for further context-specific research in severe mental illness. Holl et al [3], again, focus on the abidance of recommendations on pharmacological treatment of internationally published treatment guidelines of anxiety disorders. Screening data of 2573 psychiatric inpatients with the respective diagnosis (phobia, panic disorder, generalized anxiety disorder, other diagnosis of anxiety) filed in the international drug safety program in psychiatry (AMSP), the authors found that all diagnostic groups were only partially treated in accordance with international treatment guidelines, for which reason they see a strong need for a better implementation of recommendations in primary and secondary care.…”
mentioning
confidence: 99%
“…Anyhow, there still is a need for further context-specific research in severe mental illness. Holl et al [3], again, focus on the abidance of recommendations on pharmacological treatment of internationally published treatment guidelines of anxiety disorders. Screening data of 2573 psychiatric inpatients with the respective diagnosis (phobia, panic disorder, generalized anxiety disorder, other diagnosis of anxiety) filed in the international drug safety program in psychiatry (AMSP), the authors found that all diagnostic groups were only partially treated in accordance with international treatment guidelines, for which reason they see a strong need for a better implementation of recommendations in primary and secondary care.…”
mentioning
confidence: 99%